PENGARUH MEDIA SOSIAL DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK SOPHIE MARTIN DI KOTA KLATEN - Verayani Rahma Nur Damasita; Nur Hidayat, Erwan (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
The research conducted is survey research, the data collected are secondary data and primary data by taking people in the city of Klaten who are members of the WhatsApp business platform as the object of research. Data collection is in the form of a list of questions (questionnaires) both open and closed questions. The results of the research using the IBM SPSS version 28.0 program stated that social media has a very strong influence on purchasing decisions for Sophie Martin products in the city of Klaten as evidenced by the number of consumers who buy and know about Sophie Martin products through social media as much as 37%. Meanwhile, lifestyle has an influence on purchasing decisions for Sophie Martin products. While the correlation analysis states that lifestyle affects 22.5%. So it can be concluded that social media has a greater effect on purchasing decisions for Sophie Martin products.